"Nie mamy tu miasta trwałego". Edyta Stein o bycie wiecznym - Grzegorczyk, Anna (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
In this article I analyze the cognitive possibilities lying on the boundary of the finite and eternity being with reference to Saint Thomas Aquinas and Edith Stein’sthought. According to Saint Thomas, the rational cognition, which covers what is calleda natural world, is the highest form of knowledge and fixes its limit. Edith Stein, on thecontrary, claims that a mystical cognizance, which bases on experience and empathy,enriched by the message of the Gospel, should complement the rational one. What’scommon in those two concepts is a reference to God’s grace – the moments of revelationenlighten the efforts of human intellect. Thus knowledge on the eternal being merges both natural and supernatural cognizance.